2016
DOI: 10.1121/1.4970139
|View full text |Cite
|
Sign up to set email alerts
|

Affricate-fricative perception in Korean listeners: Evidence for universal and language specific biases

Abstract: Although language experience has a profound impact on phonetic perception, there is increasing evidence that phonetic perception is also shaped by universal biases which can be revealed as asymmetries in discrimination performance. In the present study, we explore potential perceptual asymmetries in adult Korean perception of four English affricate-fricative contrasts. Korean adults completed a native-language assimilation task and a category-based AX discrimination task with the phonemic contrast /tʃa-sa/ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous imaging work has identified several brain regions that could act as hubs for fusion of AV percepts, including but not limited to the following: the posterior STS/G (Calvert et al, 2000;Beauchamp et al, 2004Beauchamp et al, , 2010Erickson et al, 2014), middle STS (Miller and D'Esposito, 2005;Venezia et al, 2017), middle temporal gyrus (Beauchamp et al, 2004), and superior parietal lobule (Molholm, 2006). However, the findings of these studies do not categorically link these networks with fusion of AV percepts per se.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous imaging work has identified several brain regions that could act as hubs for fusion of AV percepts, including but not limited to the following: the posterior STS/G (Calvert et al, 2000;Beauchamp et al, 2004Beauchamp et al, , 2010Erickson et al, 2014), middle STS (Miller and D'Esposito, 2005;Venezia et al, 2017), middle temporal gyrus (Beauchamp et al, 2004), and superior parietal lobule (Molholm, 2006). However, the findings of these studies do not categorically link these networks with fusion of AV percepts per se.…”
Section: Discussionmentioning
confidence: 93%
“…Prior AV and visual-only studies demonstrated that vision activates low-and high-level regions of the auditory cortex (Calvert et al, 1997;but Bernstein et al, 2002;Ghazanfar et al, 2005;Kayser et al, 2008Kayser et al, , 2010Okada et al, 2013). Ghazanfar et al (2005) showed that species-specific face and voice integration takes place in the core and lateral belt of the auditory cortex, the same regions that give rise to the N1 AEP in humans (Scherg et al, 1989;Zouridakis et al, 1998).…”
Section: Discussionmentioning
confidence: 99%